SOLAR POWER PLANT PLANNING WITH TILE MODIFICATION FOR SOLAR PANEL INSTALLATION - sagita rochman; Achmad Alfianto (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
Solar power plants have been created using solar cells as power plants. This power plant utilizes the source of sunlight as its source.solar cell as receiving sunlight as a source of electricity. Utilization of sunlight to become electrical energy, Designed from tile as a medium and solar cell as a receiver of solar energy into electrical energy. Where batrai as a charging to be used, this tile as a tool planted solar cell so that it can be used tools that generate electrical energy. Solar power is one of the environmentally friendly renewable energy sources. Solar power is utilized by solar power plants to generate electricity. The electrical energy generated is the light energy converted by solar cells. The solar cell pool is arranged in such a way that it produces solar panels. The resulting electrical energy will be stored in a medium called.